Accessory liver lobes: About three observations - Crestanello, Francisco A.; Gomez Fossati, Carlos; Delgado, Bolivar (Cirugía del Uruguay, 1971)
The authors describe three cases of accessory hepatic lobes: two of them juxtavesicular and one in the lesser omentum. Bibliography is revised for similar cases and their clinical significance and probable origin is discussed.